Preliminary efficacy of a digital therapeutics smartphone application for methamphetamine use disorder: An experimental study - Zhang, Liqun; Li, Nan; Li, Yuanhui; Zhang, Tianjiao; Li, Dai; Liu, Yanru; Liu, Xiang; Hao, Wei (Frontiers in Psychiatry, 2022)
Methamphetamine is the most widely used illicit drug in China. Treating methamphetamine use disorder (MUD) is challenging due to the lack of effective pharmacotherapies. This study is an experimental study to investigate the efficacy of smartphone-based digital therapeutics in treating MUD at the community level. One hundred participants were recruited and randomized into a digital therapeutics (DTx) group (n=52) and a treatment as usual (TAU) group (n=48). The DTx group used a smartphone application to deliver cognitive behavioral therapy, approach bias modification, cognitive training, and contingency management for eight weeks. The TAU group received counseling from social workers. Cue-induced craving, cognitive functions, PHQ9, and GAD7 were measured at baseline and post-intervention. Wilcoxon tests were performed with bootstrap and multiply imputation to estimate the treatment effect size. The DTx group showed a significant reduction in drug craving (Wilcoxon effect size =-0.267, 95% CI =[-0.435,-0.099], p=0.002) and a significant improvement in cognitive function (Wilcoxon effect size =0.220, 95% CI =[0.009,0.432], p=0.041). The DTx group had overall 1-week, 8-week, and 30-week attritions of 8%, 11.5%, and 55.8%, respectively. The study shows that Digital therapeutics is feasible and potentially beneficial as a complement to community substance use treatment programs.